ANALISIS DAYA DUKUNG LAHAN BERDASARKAN KETERSEDIAAN DAN KEBUTUHAN AIR DI DAERAH ALIRAN SUNGAI JLANTAH HULU KABUPATEN KARANGANYAR TAHUN 2013 (UNTUK SUBSTANSI PEMBELAJARAN GEOGRAFI PADA KOMPETENSI DASAR PEMANFAATAN DAN PELESTARIAN LINGKUNGAN HIDUP KELAS XI - Yunanto, Muhammad Kholiq (Pendidikan Geografi, 2014)
ABSTRACT Muhammad Kholiq Yunanto. K5410043. Analysis of Land Carrying Capacity Based on The Supply and demand of water in the Jlantah Hulu Watershed Karanganyar at 2013 (for Learning Enrichment Geography substance in the Basic Competence of Environmental Utilization and Conservation for 8th Grade, 2nd Semester). Thesis, Teacher Training and Educational Faculty Sebelas Maret University. Surakarta. October 2014.This research aims to: (1) determine the level of water suplly in the Jlantah Hulu watershed at 2013, (2) determine the level of water demand in the Jlantah Hulu watershed at 2013, (3) determine the land carrying capacity between supply and demand of water level in the Jlantah Hulu watershed at 2013, (4) determine the direction of spatial planning in the Jlantah Hulu watershed at 2013 based on the level of supply and demand of water, and (5) to draft geography teaching materials on the basic competence of Environmental utilization and conservation for 8th grade, 2nd semester.This research is a descriptive research type, in which data collection and analysis methods supported by secondary data. Spatial approach was used in this study, while the population are the unit of watershed and land units in the Jlantah Hulu watershed. The implementation of this research using purposive sampling technique, and observation, documentation, interviews, and laboratory testing was used for data acquisition. The data analysis technique used to determine the water balance is done by comparing the water supply based on the water balance Thornwaite-Mather method and the water demand using Dumairi formulation. Spatial layout directives based on the function of the region by the method of scoring and weighting is done as the final outcome of this study.The results of this study concluded that (1) the water supply in the Jlantah Hulu watershed at 2013 was 42,071,119 m3, with the highest water supply in February was 10,590,853 m3, (2) the water demand in the Jlantah Hulu watershed at 2013 was calculated based on the use of land in the form of fields, irrigation (paddy), other forest, and settlements with a total water demand of 23,592,019.6 m3, (3) the carrying capacity of water resources in the Jlantah Hulu watershed at 2013 based on a comparison between the supply potential of water to the demand potential water is 1,783, so that there has been a surplus of water, (4) The arrangement of space on Jlantah watershed in 2013 based on the level of availability and water demand by classifying into 4 types of land use that other forest by 55%, rice fields by 10%, moor by 27% and settlement unchanged at 8%. Keywords: Land Carrying Capacity , Water Resources, Water Supply, Water Demand, Water Balance,